Counting scars. Memory, history and power surrounding the censorship of rock in Cuba - Hernández Castro, Junior Alfredo (Southern perspective / Perspectiva austral, 2024)
Introduction: The article examines the censorship of rock in Cuba and its impact on the collective memory of the rock community. Through an approach based on oral history and the genealogy of power, the author reconstructed testimonies of musicians and fans of the genre who suffered state repression. The censorship, which began in the 1960s, was based on a combination of political paranoia, machismo and excessive revolutionary idealism. Despite the state's partial recognition of rock in recent years, episodes of repression continue to be minimized or denied in official discourse.Development: The analysis focused on the construction of memory and its use as a tool of resistance. Based on theorists such as Foucault, Ricoeur and Jelin, the author explored how individual and collective memories have been shaped by power. Events such as the controversy over the statue of John Lennon in Havana and the closure of Maxim Rock in 2023 were mentioned, both of which showed the use of institutional forgetting as a political strategy. In addition, the role of rock as a vehicle for denunciation was highlighted, with Cuban bands who have captured the experience of repression in their lyrics. The author also identified a phenomenon of “silence-forgetfulness”, in which some victims omit or modify their stories to avoid conflict or to preserve their livelihoods.Conclusion: The study revealed that the censorship of rock in Cuba not only affected individuals, but also shaped a struggle of memory and collective resistance. Despite state attempts to rewrite history, the rock community has used various platforms, from music to social networks, to preserve and vindicate their experiences. The collective memory of censorship remains alive as a form of cultural and political resistance.